An Application of the System of National Accounts to Forest Resource Accounting of Malaysia - Billah, Ahm. Mustain (2000)
Malaysia is endowed with an extensive forest resource base. The forest area has declined by 23.0% over the last 25 years from 7,583 thousand ha in 1972 to 5,820 in 1996. Yet, the Peninsular Malaysia economy has grown 7.6% in 1974 to 8.8% in 1996 suggesting that the economy is growing sustainably. Nevertheless, there is a trend of forest conversion to make way for development. The share of forest resource rent (net price) of Peninsular Malaysia to its GDP has declined very rapidly from 0.5% in 1972 to 0.25% of GDP in 1996. This reduction implies wavering importance in relative terms but is not true in terms of absolute value. The present system of national accounts (SNA), the concept of capital maintenance applies to physical capital only. Limited account is given to the contribution of natural resource and environment to economic activities. Despite agreement among those who favour economic integrated accounts to incorporate natural capital directly into the SNA, no consensus has yet been reached to accomplish the task. The study applies the user cost method in estimating the resource depletion in forestry. According to the user cost method, the annual forestry sector real adjusted gross domestic product (AGDP) increased for the study period. Despite, decreasing physical stock of forest resources income increased due to an appreciation of the real value of resource rent. However, the net price method provided contrasting findings. The user cost is considered to be the better method in the estimation of resource depletion as it unlike the net price method takes into account the future benefits foregone or gained. For the national economy, using both the methods, the study found that the trend of per capita real ANDP and AGDP increased almost three times over the last 25 years, indicating welfare increase. Both the weak sustainability test (PAM>O) and the World Bank (1995) Genuine Saving sustainability test confirm the economic sustainability of Peninsular Malaysia with respect to forestry resource depletion. It is suggestive that enough resource rents are reinvested in the economy, particularly in human resource and infrastructure development.